2022
DOI: 10.1155/2022/6284569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endogenous Endophthalmitis in Patients with and Without COVID-19 Infection

Abstract: Introduction. Endogenous endophthalmitis (EE) is an ophthalmic emergency that can have severe sight-threatening complications. Prompt diagnosis and aggressive treatment are central to the successful management of EE. In recent years, a significant increase has occurred in the number of cases of EE. Some of these individuals had a COVID-19 infection. The current study compared EE in patients with and without COVID-19 infection. Methods. All cases of EE admitted to Khalili Hospital between April 2020 and Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
4
1
1
Order By: Relevance
“…In our study, the mean age at presentation was 54.9 ± 13.3 years, consistent with findings indicating a peak incidence during the fifth decade of life [ 1 , 3 - 6 , 8 , 9 , 14 - 20 ]. Despite certain previous reports of a male predominance [ 2 - 4 , 6 , 8 , 14 , 16 , 19 , 21 , 22 ], our study observed a higher incidence among women (55.0%), which tallied with studies reported by Michael et al and Namvar et al [ 9 , 23 ]. Left-eye involvement was observed in 58.3% of our patients.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our study, the mean age at presentation was 54.9 ± 13.3 years, consistent with findings indicating a peak incidence during the fifth decade of life [ 1 , 3 - 6 , 8 , 9 , 14 - 20 ]. Despite certain previous reports of a male predominance [ 2 - 4 , 6 , 8 , 14 , 16 , 19 , 21 , 22 ], our study observed a higher incidence among women (55.0%), which tallied with studies reported by Michael et al and Namvar et al [ 9 , 23 ]. Left-eye involvement was observed in 58.3% of our patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In 71.4% of cases of endogenous endophthalmitis secondary to liver abscess, we observed that Klebsiella pneumoniae were found to be positive, consistent with other published studies [ 19 , 21 , 22 , 27 ], suggesting close monitoring of patients with such infections. With regards to the visual outcome, we did not find any significant association between Klebsiella species and poor visual outcomes, in contrast with Chen et al and Ghiam et al [ 21 , 28 ]. Liver abscesses are associated with Klebsiella pneumoniae due to its ability to trigger a metastatic infection, particularly in individuals with conditions such as diabetes or chronic liver disease.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations